y=(e^x-e^-x)/(e^x+e^-x) 求导数
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 16:15:40
y=(e^x-e^-x)/(e^x+e^-x)求导数y=(e^x-e^-x)/(e^x+e^-x)求导数y=(e^x-e^-x)/(e^x+e^-x)求导数y=(e^x-e^-x)/(e^x+e^-x
y=(e^x-e^-x)/(e^x+e^-x) 求导数
y=(e^x-e^-x)/(e^x+e^-x) 求导数
y=(e^x-e^-x)/(e^x+e^-x) 求导数
y=(e^x-e^-x)/(e^x+e^-x) =(e^2x-1)/(e^2x+1),(分子分母同乘:e^x)
=[(e^2x+1)-2]/(e^2x+1)
=1-2/(e^2x+1)
y'=-2*(-1)*1/(e^2x+1)^2*(e^2x+1)'
=2/(e^2x+1)^2*e^2x*(2x)'
=4e^2x/(e^2x+1)^2
y=(e^x-e^-x)/(e^x+e^-x)=(e^2x-1)/(e^2x+1)=1-[2/(e^2x+1)]
y'=2(e^2x+1)'/(e^2x+1)²=2(2e^2x)/(e^2x+1)²=4(e^(2x))/(e^(2x)+1)²
y=e^x+e^-x/(e^x-e^-x)
数学期望E(E(x))=?,E(E(y))=?,E(E(x)E(y))=?应该是E(E(x))=E(x),E(E(y))=E(y),E(E(x)E(y))=E(x)E(y)
y=(e^x-e^-x)/2
统计学证明E(X-Y)=E(X)-E(Y)
E(x-y)=E(x)-E(y)的证明
E[E(X|Y)]=E(x) 怎么证明
求解常微分方程,y-y'=(e^x-e^(-x))/(e^x+e^(-x) )
E[(X-E(X))*(Y-E(Y))]=E(XY)-E(X)*E(Y)这个公式怎么证明?
[e^(x+y)-e^x]dx+[e^(x+y)-e^y]dy=0求通解
y=(e^x-e^-x)/(e^x+e^-x) 求导数
求导 y=(e^x-e^(-x))/(e^x+e^(-x))
求导:y=[e^x-e^(-x)]/[e^x+e^(-x)]
y=x^e+e^x+ln x+e^e,求Y'
∫ e^x-e^(-x)dx=e^x+e^(-x)|=e+1/e-2
E{E[E(X)]}=?
y=3^x*e^x-2^x+e求导
关于cov(x,y)=E(XY)-E(X)E(Y)的问题Cov(X,Y)=E(XY)-E(X)E(Y),可不是E(XY) =E(X)E(Y)吗?这两个E(XY)不一样吗?
y=x+e^x,x